P1855ONLINE PATIENT/CAREGIVER EDUCATION ON HYPERKALEMIA CAN IMPROVE KNOWLEDGE AND COMPETENCE AS WELL AS PROMPT REAL LIFE CHANGES. (6th June 2020) - Larkin, Amy; Blatherwick, Don
Abstract: Background and Aims: Managing hyperkalemia with a strict diet is limiting and difficult for patients. We sought to measure the impact of online education for patients/caregivers on knowledge and confidence as well as prompting change in daily life. Method: The patient/caregiver education was designed as 2 online, interactive activities. Both were comprised of text and integrated visuals; the second also included a patient commentary video. Demographic questions were asked prior to starting the education. A knowledge question was asked both before and after the activity to assess learning gains, as well as intent to change and confidence questions at the end. Absolute improvements were calculated for pre/post questions. The activities launched in April and May of 2019, and data collected through October 2019. Results: To date, 98, 462 learners have participated in the patient/caregiver activity. Activity 1: High Potassium: Causes and reasons to Treat Participants: 60, 060 Completers of all questions (included in outcomes analysis): 7, 262 Demographics: 59% female; 49% white, non-Hispanic; 66% over the age of 54; 16% have hyperkalemia, 75% were interested in learning more about the condition Knowledge changes: 13% improvement in understanding what causes hyperkalemia (46% pre to 59% post) Intent-to-act: 66% plan to talk to an HCP about next steps for treating hyperkalemia Confidence changes: 82% reported increased confidence understanding why it's important to treat hyperkalemia Activity 2: It's Complicated: How to Manage High Potassium and Heart Failure Participants: 38, 402 Completers of all questions (included in outcomes analysis): 3, 816 Demographics: 60% female; 63% white, non-Hispanic; 69% over the age of 54; 58% were interested in learning more about the condition and 25% have this condition Knowledge changes: 13% improvement in recognizing how potassium levels effect the heart (76% pre to 89% post) Intent-to-act: 64% plan to talk to their healthcare provider about a plan to manage my hyperkalemia Confidence changes: 82% reported increased confidence understanding how important is it to manage my heart failure and hyperkalemia Conclusion: The metrics and outcomes gathered in this assessment are a strong indicator that these patient/caregiver-focused online educational activities improved knowledge and confidence, and prompted intent to act by patients/caregivers related to hyperkalemia.